More than 100 years of neglect: a bibliometric analysis of global research on noma (cancrum oris). (18th October 2021) - Dominic, Catherine; Farley, Elise; Elkheir, Natalie
ABSTRACT: Background: Research plays a significant role in quantifying and addressing the burden of disease, improving healthcare delivery and developing evidence-based policy for neglected tropical diseases (NTDs). Since noma is not a recognised NTD by the World Health Organization (WHO), research activity is hypothesised to be low. This study aims to understand patterns and trends of research conducted on noma, to understand the patterns of citations, highlight networks of collaboration and analyse stakeholders in noma research. Methods: The SCOPUS database was selected and searched. Data analysis was conducted using the bibliometrix package for R in RStudio. Areas of interest included the distribution of research output on noma by year and location, the academic impact of publication output, mapping the major academic community and conducting a thematic analysis of high-frequency keywords. Results: A total of 208 documents were identified. The annual growth rate of publications is 4.3%. The average number of citations per publication was 11.0 (rounded from 10.98) and the average citations per year per publication was 0.57. The USA was the country with the highest percentage 10.6% (n=22) of corresponding authors, followed by Nigeria (6.7% [n=14]), the UK (6.3% [n=13]) and India (5.8% [n=12]). For those papers with multiple authors, there was an average of 3.22 co-authors per document. The collaboration index was 3.3. Upon plotting collaboration networks between authors, only 11 clusters were identified (frequency and intensity of collaboration). Mapping of trending topics showed a focus on skin grafting and transplantation within the literature. Conclusions: In order to progress towards eventual elimination of noma it is key that more research should be undertaken and more interest and funding should be dedicated to work on noma. Recognition of noma as an NTD by the WHO would be a first step in moving towards increased awareness.